Impact of audit committee characteristics on financial performance of listed banks in the Colombo stock exchange in Sri Lanka - Anojan, V. (University of Jaffna, 2023)
Agency theory highlights that the board of directors is running companies on behalf of the shareholders of companies. Corporate governance plays a vital role in the effective and efficient performance of listed banks in Sri Lanka. Especially, the audit committee has the responsibility to ensure the effective and efficient operations, reliability of financial reporting, and legal compliance of listed banks. The main objective of the study is to identify the impact of audit committee characteristics on the financial performance of listed banks in Sri Lanka. There are 12 listed banks in Sri Lanka on 01.01.2022, this study covers all listed banks. Data for the study were collected from the published audited financial statements and annual reports by the respective listed banks from 2016 to 2021. Descriptive and regression analyses were performed by using EViews version 8 in this study. Regression analysis confirms that audit committee characteristics have a significant impact on the financial performance of listed banks in Sri Lanka. The study strongly recommends that audit committee characteristics are much more important for the financial performance of listed banks. Further, the top management of listed banks should follow and consider effective and efficient audit committee characteristics for the healthy financial performance of listed banks. Policymakers should consider some code of best practices regarding the number of audit committee meetings and audit committee expertise.
Keywords: Audit committee characteristics; Financial performance; Listed banks